Experimental Analysis on Effect of Temperature on Performance Testing for Heat Exchangers. Issue 1 (July 2020) - Ren, Bin; Tang, Xiaoying; Pu, Zhe
Abstract: Heat exchangers are utilized to transfer or recover thermal energy in different industrial, domestic and commercial uses. With the outbreak of oil crisis, new type heat exchangers and heat transfer enhancement technology have gained more and more attention. Performance testing is the only approach to get heat transfer and flow resistance characteristics. Compared with testing standard GB/T 27698-2011, the qualitative temperatures of hot and cold fluid in TSG R0010-2019 are set as 60±1°C and 30±1°C. In this paper, the effect of qualitative temperature on performance testing for heat exchangers was investigated experimentally. The heat transfer and flow resistance correlations were obtained using Wilson plot method when the qualitative temperatures of hot water were 60°C and 70°C. And these two correlations were also developed by equal flowing velocity method at the qualitative temperatures of 50°C and 60°C. The results showed that qualitative temperature had scarcely any effect on fitting heat transfer and flow resistance correlations. The research results will provide a foundation for the actual performance testing and standard revision for heat exchangers.